Back-turn Approach for Optimal Operation of Booster Pump Systems - Y. S. Bae; M. D. Islam; Y. D. Choi; H. J. Kang; S. J. Tae; H. H. Kim (Journal of Applied Fluid Mechanics, 2025)
Conventional pumping techniques frequently fail to optimize energy use in commercial and residential high-rise buildings. This study examines creative scheduling and operational techniques with an emphasis on back-turn operations that improve operational efficiency and save energy in booster pump systems. In addition, the study demonstrates significant energy use savings while preserving system efficiency by examining water consumption trends in high-rise residential and commercial buildings. Over 24 h of back-turn operations key findings showed power usage reductions of up to 5.05% in residential units and 5.84% in commercial buildings. With the use of sophisticated control systems and real-time data monitoring, the back-turn operating approach dynamically modifies pump sequences to optimize efficiency. In addition to saving energy, this method prolongs the pump’s life by avoiding ineffective high-flow operations. The findings highlight the significance of strategic pump management as an economical and sustainable solution for urban water delivery systems, particularly in rapidly developing areas. Altogether, this study emphasizes the necessity of flexible management strategies to address energy inefficiencies, supporting the long-term expansion of urban infrastructure.